PREVALENCE OF HYDATID DISEASE IN IRAQ: A STATISTICAL STUDY (2023) - Jassim, Sura Emad; Hasoob Mohammed, Simaa (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Hydatid disease (cystic echinococcosis), caused by the larval stage of Echinococcus granulosus, remains a persistent public health concern in Iraq, particularly in areas with suboptimal livestock management and healthcare infrastructure. This study aimed to assess the national prevalence of hydatid disease across various demographic and geographic dimensions using recent official data. Method: A retrospective descriptive analysis was conducted using epidemiological data from the Iraqi Ministry of Health’s Division of Infectious Diseases, encompassing 478 confirmed cases reported in 2023. The dataset was analyzed based on age, gender, and governorate of residence using frequencies and percentages. Results: Females represented 64.9% of infections, with the 20–44 age group being most affected. The highest prevalence was found in Al-Muthanna province (1.12 per 10,000 population), indicating potential epidemiological hotspots driven by ecological and sociocultural factors. Novelty: This study provides an up-to-date national epidemiological snapshot of hydatid disease in Iraq using 2023 data, highlighting gender- and age-based vulnerability and identifying geographic clusters. The findings offer valuable insights for region-specific public health interventions and contribute new empirical evidence to the limited literature on zoonotic disease distribution in Iraq.